Reaction Kinetics of Phenolic Antioxidants Toward Photoinduced Pyranine Free Radicals in Biological Models - Aspee-Lamas, A; Cardenas-Jiron, G; Pino-Lopez, E; Aliaga-Silva, C; Zúñiga-Núñez, D (American Chemical Society, 2017)
8-Hydroxy-1,3,6-pyrenetrisulfonic acid (pyranine, PyOH) free radicals were induced by laser excitation at visible wavelengths (470 nm). The photochemical process involves photoelectron ejection from PyO- to produce PyO• and PyO•- with maxima absorption at 450 and 510 nm, respectively. The kinetic rate constants for phenolic antioxidants with PyO•, determined by nanosecond time-resolved spectroscopy, were largely reliant on the ionic strength depending on the antioxidant phenol/phenolate dissociation constant. Further, the apparent rate constant measured in the presence of Triton X100 micelles was influenced by the antioxidant partition between the micelle and the dispersant aqueous media but limited by its exit rates from the micelle. Similarly, the rate reaction between ascorbic acid and PyO• was markedly affected by the presence of human serum albumin responding to the dynamic of the ascorbic acid binding to the protein. © 2017 American Chemical Society.